Impact of Blockchain in Food Supply Chain: Enhancing Visibility and Operational Efficiency - Vasanthraj (Curtin University, 2024)
Food can become unsafe at any point from farm to fork. This study employs a mathematical model to assess blockchain’s impact on FSC visibility and operational efficiency. Secondly, a framework is proposed for an Australian milk supply chain with blockchain, Internet of Things and cloud, performing a cost and visibility analysis. Thirdly, vehicle routing optimization in a conventional DSC is compared with that of a blockchain-based DSC with the help of a case study of Gippsland DSC.